Beban Kerja Tenaga Rekam Medis di Rumah Sakit - Garis Gemilang (MEDICORDHIF Jurnal Rekam Medis, 2015)
ABSTRACT A quality medical record should be supported by the right medical record quality, available quickly and correctly. This is where medical record officer becomes the main factor in conducting a good medical record service. From the observation in Medical Record Installation in Griya Puspa RSUP Persahabatan, the writer found that there is a double job, or one medical recorder workload is as double worker, so this result in some work which not finished in time. As an example, a person in charge of managing the hospitalized hospital records, start from assembling to coding, is alsodoing statistical reports pf the hospital, while inpatients worker focused more work on outpatient treatment from taking, distribution to re-storage of medical records. Is the staff of 8 people already in accordance with the existing workload? Research Objectives Analyze Workload of Medical Record Officer in Medical Record Installation in Griya Puspa RSUP Persahabatan. This research uses descriptive method that is a method of research conducted with the main purpose to create a picture or description of a situation objectively. From the results of the above observations, obtained the total amount of personnel required by the medical record at the Medical Record Installation in Griya Puspa RSUP Persahabatan is 9 people, while the reality on the field there are 8 officers. So the conclusion of this study required the addition of 1 more person to maximize medical record services in accordance with the existing workload. ABSTRAK Rekam medis yang berkualitas harus di dukung oleh mutu rekam medis yang tepat, cepat dan benar. Dimana petugas rekam medis menjadi faktor utama dalam melaksanakan penyelenggaraan rekam medis. Dari hasil pengamatan di Instalasi Griya Puspa RSUP Persahabatan terdapat pekerjaan ganda, atau satu orang petugas rekam medis mengerjakan pekerja rangkap, sehingga ada pekerjaan yang tidak terselesaikan pada waktunya. Seperti contoh seorang penanggung jawab mengerjakan pengelolaan rekam medis rawat inap mulai dari assembling hingga koding sekaligus mengerjakan laporan statisktik rumah sakit sedangkan petugas rawat inap lebih banyak mengerjakan pengolahan rawat jalan mulai dari mengambil, distribusi hingga penyimpanan kembali rekam medis. Apakah dengan petugas yang berjumlah 8 orang sudah sesuai dengan beban kerja yang ada? Tujuan penelitian Menganalisa Beban Kerja Petugas Rekam Medis di Instalasi Griya Puspa RSUP Persahabatan. Penelitian ini menggunakan metode deskriptif yaitu suatu metode penelitian yang dilakukan dengan tujuan utama untuk membuat gambaran atau deskripsi tentang suatu keadaan secara objektif. Dari hasil pengamatan diatas, didapat jumlah keseluruhan tenaga yang dibutuhkan oleh bagian rekam medis di Instalasi Griya Puspa RSUP Persahabatan adalah 9 orang, sedangkan kenyataan dilapangan terdapat 8 orang petugas. Jadi kesimpulan penelitian ini diperlukan penambahan 1 orang lagi untuk memaksimalkan pelayanan rekam medis sesuai dengan beban kerja yang ada.